Pengaruh earning per share (eps), price earning rasio (per), ukuran perusahaan (firm size) dan risiko sistematis (beta) terhadap return saham pada perusahaan real estate & property yang terdaftar di bei tahun 2006-2009 - Tiara Dewi Sundari; Hardi '; Poppy Nurmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research was undertaken to test and provide empirical evidence of the influence of Earning Per Share (EPS), Earning Price Ratio (PER), company size (Firm Size) and Systematic Risk (BETA) on stock returns of real estate & property companies listed on the Stock Exchange . Population is the number of whole objects (entities or individuals) whose characteristic are about to suspected. In this study population were observed and all Real Estate & Property companies listed in Indonesia Stock Exchange in 2006 to 2009 as many as 139 companies.Based on the research results which indicate that EPS significantly influence stock returns. The effect that is positive, namely the level of EPS can certainly improve the quality of the audit. PER significant effect on stock returns. This showed that the effect was significant. PER models that based on the ratio between the stock price per share with EPS which can increase stock returns. Firm size have a significant effect on stock returns, the company size (Firm Size) is a large scale which can be classified as big and small firms, systematic risk has no effect on stock returns.Recommendations can be submitted at the next study is should add a longer observation period to obtain more accurate results. With add the period in the next research by using more samples to be more accurate.Keywords : Per Share (EPS), Price Earning Ratio (PER), company size (FIRM SIZE), Systematic Risk (BETA) Stock Return